Intermediate band formation in a δ-doped like QW superlattices of GaAs/AlxGa1−xAs for solar cell design. (March 2018) - Del Río-De Santiago, A.; Martínez-Orozco, J.C.; Rodríguez-Magdaleno, K.A.; Contreras-Solorio, D.A.; Rodríguez-Vargas, I.; Ungan, F.
Abstract: It is reported a numerical computation of the local density of states for a δ -doped like QW superlattices of Al x Ga1− x As, as a possible heterostructure that, being integrated into a solar cell device design, can provide an intermediate band of allowed states to assist the absorption of photons with lower energies than that of the energy gap of the solar-cell constituent materials. This work was performed using the nearest neighbors s p 3 s * tight-binding model including spin. The confining potential caused by the ionized donor impurities in δ -doped impurities seeding that was obtained analytically within the lines of the Thomas-Fermi approximation was reproduced here by the Al concentration x variation. This potential is considered as an external perturbation in the tight-binding methodology and it is included in the diagonal terms of the tight-binding Hamiltonian. Special attention is paid to the width of the intermediate band caused by the change in the considered aluminium concentration x, the inter-well distance between δ -doped like QW wells and the number of them in the superlattice. In general we can conclude that this kind of superlattices can be suitable for intermediate band formation for possible intermediate-band solar cell design. Highlights: δ -doped quantum well like Superlattice as a mechanism to generate intermediate bands. Spacer layer as a mechanism to control the intermediate band-width in Superlattices. Al concentration can modify intra-subband energy gap for solar cell device design.